Determine of caffeine using HPLC and other quality characteristics in different brands of coffee / Nor Aishah Akmal A. Rahman - A. Rahman, Nor Aishah Akmal (2005)
Determination of caffeine in coffee was done using HPLC. The main objective of the analysis is to determine the caffeine conteiit in various coffee brands. Highest caffeine concentration was detected in Kapal Api roasted coffee which was 137.61 ppm. The lowest concentration of caffeine was obtained in Boh decaffeinated coffee with 11.29 ppm. Physical analysis of moisture content, ash and colour of coffee were also carried out to compare the quality characteristic between different coffee samples. The highest percentage of moisture content was obtained in Nescafe decaffeinated coffee which was 4.10%. The highest percentage of ash was found in Nescafe decaffeinated coffee. The percentage of the ash was 8.24%. Colour determination on the coffee sample was carried out using chromameter.